In-beam study of 78 Br - Behar, M.; Abriola, Daniel Hugo; Filevich, Alberto; García Bermudez, Gerardo J.; Kreiner, Andrés Juan; Mariscotti, Mario A. J.; Piston, J. A.; Barneoud, D. (North Holland Publishin Co., 1982)
Fil: Behar, M. Comisión Nacional de Energía Atómica; Argentina